HEALTHCARE INFORMATION SYSTEM MANAGEMENT IN THE KYRGYZ REPUBLIC - R. Bokushev; G. S. Kitarova; Y. I. Kondratyeva; M. S. Alymkulov (Педиатрическая фармакология, 2016)
Despite the active reformation and informatization of healthcare, healthcare establishments of different levels feature a different degree of access to information resources. The situation is also characterized by parallel development of information collection flows, different level of development of different regions, poorly developed infrastructure. These aspects complicate operative information exchange for the purposes of managerial decision-making. We need to determine the degree of compliance of healthcare information systems and subsystems with user needs, as well as assess the capabilities of information systems to provide timely and quality healthcare information to all users of all levels for the purposes of managerial decision-making. The article presents results of a comprehensive assessment of the current state of healthcare informatization in the Kyrgyz Republic using HMN-developed (Health Metrics Network) analytical tools. We demonstrate significant differences in healthcare information system management in the Kyrgyz Republic and note the heterogenous use thereof, especially in regions and districts.